Chitin-Glucan complex hydrogels: physical-chemical characterization, stability, in vitro drug permeation, and biological assessment in primary cells - Araújo, Diana (2023)
Chitin-glucan complex (CGC) hydrogels were fabricated by coagulation of the biopolymer from an aqueous alkaline solution, and their morphology, swelling behavior, mechanical, rheological, and biological properties were studied. In addition, their in vitro drug loading/release ability and permeation through mimic-skin artificial membranes (Strat-M) were assessed. The CGC hydrogels prepared from 4 and 6 wt% CGC suspensions (Na51*4 and Na51*6 hydrogels, respectively) had polymer contents of 2.40 0.15 and 3.09 0.22 wt%, respectively, and displayed a highly porous microstructure, characterized by compressive moduli of 39.36 and 47.30 kPa and storage moduli of 523.20 and 7012.25 Pa, respectively. Both hydrogels had a spontaneous and almost immediate swelling in aqueous media, and a high-water retention capacity (>80%), after 30 min incubation at 37 C. Nevertheless, the Na51*4 hydrogels had higher fatigue resistance and slightly higher-water retention capacity. These hydrogels were loaded with caffeine, ibuprofen, diclofenac, or salicylic acid, reaching entrapment efficiency values ranging between 13.11 0.49% for caffeine, and 15.15 1.54% for salicylic acid. Similar release profiles in PBS were observed for all tested APIs, comprising an initial fast release followed by a steady slower release. In vitro permeation experiments through Strat-M membranes using Franz diffusion cells showed considerably higher permeation fluxes for caffeine (33.09 g/cm2/h) and salicylic acid (19.53 g/cm2/h), compared to ibuprofen sodium and diclofenac sodium (4.26 and 0.44 g/cm2/h, respectively). Analysis in normal human dermal fibroblasts revealed that CGC hydrogels have no major effects on the viability, migration ability, and morphology of the cells. Given their demonstrated features, CGC hydrogels are very promising structures, displaying tunable physical properties, which support their future development into novel transdermal drug delivery platforms.